Hubungan Karakteristik dan Konsumsi Makanan Kariogenik dengan Kejadian Karies Gigi Pada Siswa Umur 11ï12 Tahun di Sekolah Dasar Negeri Terpilih Wilayah Kerja Puskesmas Taktakan Kota Serang - Novianus, Cornelis (ARKESMAS [Arsip Kesehatan Masyarakat], 2016)
Relationships Characteristics and Cariogenic Food Consumption Behavior With Dental Caries Incidence at Students Aged 11ï12 Years Selected The State Elementary School In The Puskesmas Taktakan Working Area Serang City 2015Introduction. Dental caries is one of the teeth and mouth disease that many experienced particularly byprimary school children. The incidence of dental caries in children is measured through Decayed,Missing, Filled Teeth (DMFT) index. Dental cariesis closely related to elementary school children in thehabit cariogenic foods consumption. In Serang City, the number of students who suffer from dental carieshighest in the Puskesmas Taktakan working area. Objective. This study aimed to determine the relationship of students characteristics and cariogenic foodconsumption behavior with dental caries incidence. Including characteristics (gender, pocket money,salivary pH), student behavior (knowledge, attitude, cariogenic food consumption, tooth brushing habit,tooth brushing method) Methods. This research was conducted with a quantitative approach to the cross sectional design. The population of the study were students aged 11ï12 yers from the State Elementar Scholl in The PuskesmasTaktakan area, Serang City. The sample selected by cluster random sampling techniques were 140students. Results. The variable that have significant relationship with the dental caries incidence are pocketmoney, attitude, cariogenic food consumption, tooth brushing habits, tooth brushing method. Meanwhile,variables that do not have a significant relationship with the dental caries is incidence is knowledge,gender, salivary pH. The most dominant factor is cariogenic food consumption variable associated withthe dental caries incidence.Conclusion. Foods that are cariogenic can damage the students teeth, so students are not eatingcariogenic food and can bring food that is not too sweet and sticky, if students who want to eat sweet andsticky foods should find the right time to eat and immediately brushed teeth because cariogenic foods can become acidic within 20ï30 minutes.Â